Distortion control in multi pass dissimilar GTAW process using Taguchi ANOVA analysis - Vemanaboina, Harinadh; Edison, G; Akella, Suresh (International Journal of Engineering and Technology, 2018)
The present study is to observe the distortion development in the weldment of Inconel 625 to SS316L multipass weldments. In this work two-level factors such as welding process, filler wire and root gap were employed with L4 orthogonal array. The welding has been carried out with continuous current and pulsed current gas tungsten arc welding process implementing ERNiCrMo-3 and ERNiCr-3 fillers rods respectively. The fractional factorial experimentation was analysis of variances (ANOVA), it was carried out to observe the critical parame-ter which influence distortion caused in the weldments. The quality of welds has been evaluated by X-Ray Radiography test. The results show that welding process and filler wire are contributing more in the distortion.Â Â